(untitled) (Texas Journal of Medical Science, 2022)
If the baby’s kidney is still immature in terms of its structure and function, it is capable of satisfactorily performing its function under physiological conditions and maintaining the stability of the internal environment. This is achieved due to the good effect of the consumed food on kidney function. The identity of the renal and urinary systems of adults and infants differ from each other in terms of ion composition, osmotic pressure and other characteristics.